Fault Tolerant Control for Remotely Operated Vehicles with Thruster Faults using Nonlinear Disturbance Observers. Issue 31 (2022) - Baldini, Alessandro; Felicetti, Riccardo; Freddi, Alessandro; Longhi, Sauro; Monteriù, Andrea
Abstract: In this paper, a disturbance observer based control strategy is developed to provide fault tolerance to thruster faults for a remotely operated vehicle. The scheme relies on the vehicle's position, orientation and velocity information only, without the need for additional measurements from the thrusters such as voltage, current, and rotation speed. Because the system is over-actuated, a bank of observers is designed for purposes of fault detection and isolation. A nonlinear disturbance observer is designed to restructure itself, according to the fault isolation outcome, to estimate the fault magnitude. The fault estimation is finally exploited by the control law using an active fault tolerant control strategy. The solution is designed for the cases where at most one faulty thruster is expected. The fault tolerant control strategy is tested in simulation, where a severe thruster fault is injected.